Orifice plate flowmeter performance under pulsating flow conditions - Idres, Moumen; Suliman, Suliman; Kafafy, Raed Ismail; Shaik Dawood, Mohd. Sultan Ibrahim (2014)
Current need for cost and energy savings increases the demand for accurate measurement of mass flow rate. Measuring flow rate through a pipe is an important process in many industries, such as natural gas transport, feeding systems in petrochemicals, automotive and hydraulic applications. Pressure differential devices such as orifice plate are used extensively because of their simplicity and low cost maintenance. When flow pulsations exist, flow measurement errors are unavoidable. In this research, the performance of an orifice plate flow meter is assessed numerically using STAR-CCM+ software. Incompressible 2-D turbulent flow is considered for Re=1.5×104 to Re=5×105. Numerical simulations of steady flow are conducted to evaluate the discharge coefficient of the orifice. The grid is chosen based on grid independency study. The discharge coefficient is compared favorably with ISO value. For unsteady flow, time independency study is conducted to determine the time step. Unsteady flow rate measurement error due to pulsation is calculated for different frequencies. The results showed good agreement between calculated mass flow rate and simulated measured mass flow rate.